Motivations for Code-mixing Sinhala into English among Teenagers - Senaratne, U. D. (Sabaragamuwa University, Sri Lanka, 2014)
In bi/multi-lingual settings most individuals have the tendency to mix words from the languages that they have access to, which is termed code-mixing. The aim of this paper was to find out the motivations for code-mixing Sinhala into English among eighty teenagers aged 15 - 16 from two selected schools in Colombo 4. The participants were selected using the simple random sampling whilst the survey technique was employed to gather data of this study. The four psycholinguistic motivations - filling the lexical gaps which arise due to language deficits and the non-availability of English terms, the relative ease of accessibility and the medium-of-learning effect - were acknowledged as reasons for code-mixing by over 50% of the respondents. Filling the lexical gaps which occur owing to the non-availability of English words was identified as the most frequent psycholinguistic motivation for code-mixing by the respondents. On the other hand, three sociopragmatic motivations (taking into consideration the interlocutor’s language proficiency, displaying affability and gaining peer recognition) were identified as motivations for code-mixing by more than 60% of the selected teenagers. Displaying membership of the social class and seeking attention were not distinguished as reasons for code-mixing by most of the respondents. The overall findings of the study gave perceptive insights into the teenager’s use of English and their attitudes towards it.
Keywords: Code-mixing; Motivations; Teenagers